79.3k views
1 vote
I forgot how to do this it looks hard someone help

I forgot how to do this it looks hard someone help-example-1

1 Answer

4 votes

Hi there! :)


\large\boxed{-4}

Use PEMDAS (Parenthesis, Exponents, Multiply, Divide, Addition, Subtraction) to simplify:


(6 - 3(2^(2)-11)+5 )/(4-36/3)

We can begin by simplifying the numerator and denominator separately:

6 - 3(2² - 11) + 5 =

Exponents:

6 - 3(4 - 11) + 5 =

Multiplication:

6 - 12 + 33 + 5 =

Add and subtract:

32

-------------------

Denominator:

Division:

4 - 36÷3 =

Subtraction:

4 - 12 = -8

Resulting fraction:


\large{(32)/(-8)} = -4

User David Benham
by
5.2k points